Effects of Burner Configurations on the Natural Oscillation Characteristics of Laminar Jet Diffusion Flames. (September 2015) - Manikantachari, K. R. V.; Raghavan, Vasudevan; Srinivasan, K.
In this work, effects of burner configurations on the natural oscillations of methane laminar diffusion flames under atmospheric pressure and normal gravity conditions have been studied experimentally. Three regimes of laminar diffusion flames, namely, steady, intermittent flickering and continuous flickering have been investigated. Burner configurations such as straight pipe, contoured nozzle and that having an orifice plate at the exit have been considered. All burners have the same area of cross section at the exit and same burner lip thickness. Flame height data has been extracted from direct flame video using MATLAB. Shadowgraph videos have been captured to analyze the plume width characteristics. Results show that, the oscillation characteristics of the orifice burner is significantly different from the other two burners; orifice burner produces a shorter flame and wider thermal plume width in the steady flame regime and the onset of the oscillation/flickering regimes for the orifice burner occurs at a higher fuel flow rate. In the natural flickering regime, the dominating frequency of flame flickering remains within a small range, 12.5 Hz to 15 Hz, for all the burners and for all fuel flow rates. The time-averaged flame length-scale parameters, such as the maximum and the minimum flame heights, increase with respect to the fuel flow rate, however, the difference in the maximum and the minimum flame heights remains almost constant.